RANCANG BANGUN ALAT CETAK KOMPOSIT SAMPAH PLASTIK DENGAN SABUT KELAPA - Priyono Priyono; Artian Sirun; Ivonne Fredika Yunita Polii (Otopro, 2021)
The plastic waste composite molding tool with coconut fiber is designed with the aim of converting HDPE plastic waste, especially drink bottle covers mixed with coconut fiber into a product in the form of a composite board (panel) that is more useful. The dimensions of the mold are 410 x 540 mm, the tool height is 850 mm, the width is 600 mm, the length is 600 mm, the temperature of the installed heating elements is around 200-250 degrees for 12 pieces, 220 V 1000 watts, while the press uses a 10 ton hydraulic jack. While the heating temperature for pressing the composite board is set in the range of 130 – 180 oC. From the results of the first printing press with iron plate material, the resulting product is sticky on the plate surface, the second test is coated with aluminum foil, the resulting product is less than perfect because the surface is uneven. , while the third test was coated with a stainless steel plate, the resulting product was better than the previous results. This research needs to be improved in order to assist the government in handling plastic waste. In addition, the results of products with this tool will help improve people's skills and improve the economy of the products of this tool.